Effects of local stress, strain, and hydrogen content on hydrogen-related fracture behavior in low-carbon martensitic steel. (15th May 2021) - Shibata, Akinobu; Yonemura, Takashi; Momotani, Yuji; Park, Myeong-heom; Takagi, Shusaku; Madi, Yazid; Besson, Jacques; Tsuji, Nobuhiro
Abstract: The present study investigated the hydrogen-related fracture behavior of specimens with different stress concentration factors through microstructure observation, finite element (FE) simulation, and digital image correlation (DIC) analysis. The alloy studied was a simple model alloy (Fe-0.2C binary alloy) with fully martensite structure. When the hydrogen content was large (2.21 mass ppm (121 at ppm)), the crack initiation and propagation occurred along the prior austenite grain boundaries. Through the FE simulations, we found that the crack initiation sites corresponded to the region with high stress and high hydrogen content. Although the stress concentration factors were different, the stress level and the hydrogen content at the crack initiation sites were almost the same, indicating that the hydrogen-related intergranular fracture originated from stress-controlled decohesion at the prior austenite grain boundaries. For the specimen with small hydrogen content (0.41 mass ppm (22.5 at ppm)), the quasi-cleavage cracks formed at the surface of the notch root and propagated along the 011 planes. The FE simulations revealed that the plastic strains were maximum at the initiation sites of the quasi-cleavage cracks. Moreover, we confirmed that hydrogen enhanced the local plastic deformation by DIC analysis. As the local values of maximum principal stress, plastic strain, and hydrogen content at the initiation sites of the quasi-cleavage cracks were different depending on the stress concentration factor, the critical quantitative condition for the initiation of quasi-cleavage cracking was not simple compared to that of the case of intergranular cracking. Graphical abstract: Image, graphical abstract